2008
DOI: 10.1096/fj.08-106187
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament protein synemin contributes to the migratory properties of astrocytoma cells by influencing the dynamics of the actin cytoskeleton

Abstract: We have shown previously that, in astrocytoma cells, synemin is present at the leading edge, an unusual localization for an intermediate filament (IF) protein. Here, we report that synemin down-regulation with specific small hairpin RNAs (shRNAs) sharply decreased the migration of astrocytoma cells. The presence of synemin at the leading edge also correlated with a high migratory potential, as shown by comparing astrocytoma cells to carcinoma cells without synemin at the leading edge. Synemin-silenced astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
3
37
0
Order By: Relevance
“…Cytoskeletal reorganization of the actin filament is of central importance for cell motility and is essential for most types of cell migration. 36 Interestingly, synemin, a large IF protein structurally-similar to nestin, directly regulates F-actin and alpha-actinin in astrocytoma cells, 7,8 and is localized at their leading edge, which is essential for cell migration. 37 Conceivably, nestin may have a similar role in relation to actin in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoskeletal reorganization of the actin filament is of central importance for cell motility and is essential for most types of cell migration. 36 Interestingly, synemin, a large IF protein structurally-similar to nestin, directly regulates F-actin and alpha-actinin in astrocytoma cells, 7,8 and is localized at their leading edge, which is essential for cell migration. 37 Conceivably, nestin may have a similar role in relation to actin in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cytoskeletal reorganization of the actin filament is important in cell motility and is essential for most types of cell migration (31). Previous studies have shown that synemin, one of the large IF proteins structurally similar to nestin, directly regulates F-actin and α-actinin in glioma cells (32,33). Nestin is also reported to bind to microfilaments and microtubules at the C-terminus of the protein (12).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the IF system for cell migration and process extension has become apparent in several gene knock out paradigms including keratins [Long et al, 2006], vimentin [Eckes et al, 1998;Nieminen et al, 2006], vimentin/glial fibrillary acidic protein [Lepekhin et al, 2001], and synemin [Pan et al, 2008]. The resulting altered tissue properties are apparently of relevance for wound healing [Eckes et al, 2000;Mazzalupo et al, 2003;Wong and Coulombe, 2003], homing of leukocytes [Nieminen et al, 2006], glial scar formation [Pekny et al, 1999], and axonal regeneration [Menet et al, 2003;Triolo et al, 2006;Shim et al, 2008;Toth et al, 2008].…”
Section: Discussionmentioning
confidence: 99%